MULTICULTURALISM IDEOLOGY IN THE DEVELOPMENT OF BURCEK ART IN BUDAKELING VILLAGE, KARANGASEM, BALI - Yuni Astiti, Rustiani Erwin; Suwitha, I Putu Gede; Astiti Laksmi, Ni Ketut Puji (E-Journal of Cultural Studies; Vol 17 No 4 (2024): Volume 17 Number 4 November 2024DO - 10.24843/cs.2024.v17.i04.p02, 2024)
Burcek art is a combination of Islamic Burdah and Balinese Cekepung in Budakeling Village which is full of multicultural values to convey the message of the importance of religious harmony. This research aims to dismantle the ideology of multiculturalism in Burcek art with a cultural studies approach. Data collection through observation, in-depth interviews, and document study. Data were analyzed through data reduction, data presentation and data verification, then interpretation was carried out using several critical theories. This research found that the development of Burcek art in Budakeling village was based on the spirit of multiculturalism. This spirit is what binds Hindus and Muslims in brotherhood which is represented through the Burcek art performance. The song lyrics displayed in Burcek art represent the importance of building religious harmony inherited in Budakeling Village. Overall, the collaboration in Burcek's art show also represents this ideology. Based on the findings of this research, it is recommended that Burcek art be maintained and developed as a local Balinese culture that makes an important contribution to a multicultural society. Keywords: multiculturalism, ideology, Burcek art, religious harmony